Design of Wave Glider Optimal Parameters Suitable for the Northwest Pacific Ocean, the North Indian Ocean, and the South China Sea - Xi Chen (Journal of Marine Science and Engineering, 2021)
To study the optimal design of Wave Glider parameters in the wave environment of the Northwest Pacific Ocean, the North Indian Ocean, and the South China Sea, the average velocity of a Wave Glider was taken as the evaluation criterion. Wave reanalysis data from ERA5 were used to classify the mean wave height and period into five types by the K-means clustering method. In addition, a dynamic model was used to simulate the influence of umbilical length, airfoil, and maximum limited angle on the velocity of the Wave Glider under the five types of wave element. The force of the wings was simulated using FLUENT as the model input. The simulation results show that (1) 7 m is the most suitable umbilical length; (2) a smaller relative thickness should be selected in perfect conditions; and (3) for the first type of wave element, 15° is the best choice for the maximum limited angle, and 20° is preferred for the second, third, and fourth types, while 25° is preferred for the fifth type.